High Gain Power Generation Based On Hybrid Renewable Energy for AC Load Application - Shaik Mohammad Irshad; G.P Ramesh (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
This study presents the distributed energy source based current fed inverter has generated high voltage with less passive elements. The hybrid renewable energy generation such as solar and wind has used. The single stage power generation based switched inverter has combined characteristics of both impedance source inverter and switched boost inverter. In conventional voltage source inverter has less boost ability and high electromagnetic noise immunity to the modified current fed inverter circuit. The single diode photovoltaic model and wind-based energy generation have fed into current fed switched inverter for improving high gain and high power factor. The maximum power point tracking such as incremental conductance algorithm has fast-tracking of solar power and generates continuous power to the inverter circuit. 12V solar power and wind power is designed for dc power production, and the output of dc link capacitor is 118V using current fed switched inverter. The current fed switched inverter is designed and implemented in MATLAB/Simulink environment.